Status of Arsenic Contamination and Assessment of other Probable Heavy Metal Contaminants in Ground Water of Dang District in Nepal - Mahat, RK; Kharel, RP (Scientific World, 2010)
Issue of arsenic contamination in drinking water in Terai belt has been a prevalent phenomenon in Nepal. So, this study has been conducted to visualize the status of arsenic contamination in ground water in Dang district located at central west Terai in Nepal. A total of 26,878 Tubewells and Dugwells were tested in 36 Village Development Committees (VDCs) using HACH arsenic testing field kit and 811 samples were re-tested employing Wagtech Digital Arsenator. 540 samples were analysed for confirmation by continuous flow Hydride Generation Technique using Atomic Absorption Spectrophotometer (AAS) in the DWSS laboratory. Of the total samples, 0.83% was found to contain Arsenic above WHO drinking water Qualty guidelines value of 0.01 mg/l (10 ppb) and 0.2% was found to contain arsenic above National Drinking Water Quality Guidelines value of 50 ppb. Gobardiha and Gangaparaspur are the two most affected VDCs with 1.75 and 1.16 percents of Tubewells being affected by arsenic of concentration above 50 ppb. The highest Arsenic concentration of 150 ppb was found in Bela and Gobardiha VDCs and a severe case of Arsenicosis was identified in Bela VDC. 20 samples were randomly chosen and analyzed for other heavy and trace metal contaminants like Cu, Fe, Mn, and Cd using flame AAS method. Ground water in this area seems to be affected by high concentration of Iron upto 11.01 mg/l and of Manganese upto 0.51 mg/l. Statistical tools were employed to assess the probable association among them but no significant correlation among arsenic and other metals could be retrieved. Keywords: Atomic Absorption; Spectrophotometry; Standard Reduction Potential; Arsenicosis; Heavy and Trace metals. DOI: 10.3126/sw.v7i7.3821 Scientific World Vol.7(7) 2009 pp.33-36